The excavation of a hut circle at Cùl a’Bhaile, Jura - Stevenson, J B; Dickson, Camilla A; Stenhouse, M J; Whittington, G; Wickham-Jones, Caroline R (Proceedings of the Society of Antiquaries of Scotland, 1985)
Farmstead: multiperiod hut circle in enclosure, late 2nd/early 1st millennium BC.